Characteristics and Dynamics of the Freshwater Fish Market in Chengdu, China - Fang, Julian; Fabinyi, Michael (Frontiers in Sustainable Food Systems, 2021)
The drivers and characteristics of trends in aquatic product consumption are a crucial component of fish food system sustainability. The Chinese market for aquatic products is the largest in the world, yet little has been published on the characteristics of the freshwater fish market. This Paper draws on interviews with key informants to understand the social characteristics of the freshwater fish market in Chengdu, Sichuan province. Price, food safety and quality, freshness and local culinary traditions are important influences on patterns of freshwater fish consumption. However, imported species such as pangasius and branded products are increasing in popularity, indicative of changes in the Chengdu freshwater fish market and the Chinese market for aquatic products more generally.